Migration as diplomacy: Institutionalising mobility in Nigeria–UK relations post-Brexit - Oluwakemi D. UDOH; Favour O. HAMBOLU; Ugochukwu D. ABASILIM (Faculty of Social and Political Science, Universitas Airlangga, 2026)
Migration has created a strong connection between Nigeria and the UK because of their historical ties rooted in colonialism. Following the UK’s departure from the EU, the significance of migration has become even greater, as the two nations have used it as a diplomatic tool. This paper investigates the importance of migration as a diplomatic instrument in Nigeria’s relations with the UK following the UK’s exit from the EU. The study employed a qualitative research design. The analysis reveals that changes to the British immigration system have created opportunities for Nigerian migrants, while demonstrating the UK’s desire to maintain control over its borders and the labor market. The findings indicate that migration has become a significant instrument of international diplomacy, as both parties have developed official procedures for handling immigration issues under the Migration Partnership and the Enhanced Trade and Investment Partnership agreements. The conclusion of this study shows that although both agreements link migration to a development framework, asymmetrical relations remain evident, thereby constraining Nigeria’s negotiating capacity.